أخلاق الصينيين في ضوء القرآن والسنة: دراسة لنماذج مختارة - خان، ون تشن (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study examines the concept of ethics or virtue in Islam and in the Chinese cultural definition. Ethics in this study encompasses differences that might exist between the good and bad. The relevant Quranic verses and Hadiths as well as thoughts by Muslim scholars (ulama) on the subject matter will be examined using the analytical method. The basis of the study is that believing Muslims around the world, like the Chinese, are sometimes subjected to non-religious or non-Islamic ethical values and they may not have access to the true Islamic concepts which clearly take precedence.